Video Animasi Sebagai Variasi Media Pembelajaran Mata Kuliah Akuntansi Manajemen - Rosy Aprieza Puspita Zandra; Apit Miharso; Dyah Metha Nurfitriasih (Wahana Riset Akuntansi, 2022)
This study intends to explore information about the effectiveness of using animated videos in encouraging increased understanding and student learning outcomes. The research method chosen is Quasi Experimental research, with the design of the Nonequivalent Control Group Design for a number of 60 students who are taking Management Accounting courses at the State Polytechnic of Malang. The study of effectiveness measured through the results of pre-test, post-test and student perception questionnaires showed that animated video media was quite effective in improving student learning outcomes by becoming an intermediary factor in learning by presenting ease, attractiveness, clarity. messages, increasing the variety and quality of learning. This finding is expected to contribute to providing insight into alternative accounting learning tools packaged in a more coomunicative, innovative and interactive form, especially to support the independent learning process. Keywords: learning media, animated videos, commucation, effectiveness, gain score.